FRAUD PREVENTION IN THE PERSPECTIVE OF PROBITY AUDIT (THE CASE STUDY OF UNIVERSITY X) - Putri, Dhika; Syariati, Dian; Ahmad, Arisona (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2021)
Goods and services procurement in the university sector is a big chance towards fraud case occurrence. Corruption in the university environment resulted in state loss in the amount of two billion rupiahs. Therefore, The internal auditor ofÂ  University X implements a probity audit as one effort to materialize the procurement system with low fraud possibility. The purpose of this study is to contribute to the understanding of fraud prevention using probity audits on goods and services procurement in the university sector. This research was carried out using a qualitative approach, with a case study method. The data collection was conducted by document analysis and interviews. The data obtained is then reduced, identified, and analyzed. The results conclude that the probity audit in University X is a real-time audit which one conducted in the construction and maintenance stages. Based on the internal auditor evaluation result, a probity audit rated sufficiently to prevent fraud in the goods and services procurement process in the University X.